Cyber Warfare and Terrorism 2020
DOI: 10.4018/978-1-7998-2466-4.ch084
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Money Laundering (ML) on Growth Application to the Gulf Countries

Abstract: The strategic goal of this paper is to study the effects of the prevention policies against money laundering on growth in the gulf countries (Saudi Arabia, Kuwait, Qatar, Bahrain, UAE and Oman) from 1980 to 2014. Thus, the logistic regression (logit model) had given three fundamental results. The first had shown that the main policies in matter of fight against money laundering (anti money laundering law AMLL, suspicious transaction reporting STR, the criminalizing of terrorist financing CTF) have had positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Also, AML regulations eliminate inefficient firms from the marketplace to promote growth. Issaoui et al (2016) had shown that AML policies, suspicious transaction reporting and criminalization of terrorist financing have positive growth outcomes for Gulf countries. In a study of 135 countries, Djankov et al (2006) prove that countries with better business regulations grow faster.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Also, AML regulations eliminate inefficient firms from the marketplace to promote growth. Issaoui et al (2016) had shown that AML policies, suspicious transaction reporting and criminalization of terrorist financing have positive growth outcomes for Gulf countries. In a study of 135 countries, Djankov et al (2006) prove that countries with better business regulations grow faster.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A study by Fakhri et al (2016) examined the impact of money laundering on growth through Gulf countries during 1980-2014. The findings show that the main policies in matter of fight against money laundering "suspicious transaction reporting, anti-money laundering law, and the criminalizing of terrorist financing" have significant and positive impacts on raising the possibilities to realize more economic growth.…”
Section: Prior Studies Prior Studiesmentioning
confidence: 99%